How Lithuanian mathematics teachers interpret student thinking at the different career stages - Grigaliūnienė, Monika; Rutkienė, Aušra; Lehtinen, Erno (Modestum Ltd, 2025)
This study examines the pedagogical content knowledge (PCK) of Lithuanian mathematics teachers at different stages of their professional careers. The research sample comprised 134 participants ranging from novice teachers with no teaching experience to experienced educators, with the longest career spanning 45 years. The participants were divided into four groups according to the length of their career and the results were analyzed accordingly. While no significant correlation between PCK and career length was found in the overall test results, statistically significant differences were found between them for certain questions. The results make it clear that some teachers have difficulty interpreting students’ errors and developing appropriate teaching strategies. This study indicates that further research is needed to deepen the understanding of PCK development throughout teachers’ careers and to investigate the factors that contribute to differences in PCK within groups of teachers with similar career lengths.